Bilateral superficial brachial artery - Sharma, T; Singla, RK; Sachdeva, K (Kathmandu University Medical Journal, 2010)
Variations of the upper limb arterial system are well documented. Accurate knowledge of the normal and variant arterial anatomy of the axillary artery is important for clinical procedures and vascular radiology. In this article, a rare bilateral variation of superficial brachial artery is being reported. The axillary artery on both sides divided in its third part into a superficial brachial artery passing superficial to the lateral root of median nerve and brachial artery proper. The former terminated in the cubital fossa by dividing into ulnar and radial arteries while the later descended deep to the medial root of median nerve and gave anterior and posterior circumflex humeral branches of axillary artery and profunda brachii of brachial artery. Then it terminated by giving twigs to muscles of arm. Earlier superficial brachial artery is reported with a prevalence rate varying from 0.2 - 25 % but a bilateral variation is extremely rare. Further its ontogeny and clinical implications are discussed in detail. Key words: Superficial brachial artery; brachial artery; Axillary artery DOI: 10.3126/kumj.v7i4.2768 Kathmandu University Medical Journal (2009) Vol.7, No.4 Issue 28, 426-428